2003
DOI: 10.1029/2003gl017395
|View full text |Cite
|
Sign up to set email alerts
|

Cold halocline, increased nutrients and higher chlorophyll off Oregon in 2002

Abstract: Observed changes in the nutrient levels in the halocline of the California Current during 2002 indicated a natural eutrophication that was accompanied by increased chlorophyll and oxygen in surface water. Decreased oxygen in the lower water column over the shelf indicated that much of the phytoplankton production was respired rather than passed on to higher trophic levels. In 2002 the halocline water was >1°C colder than usual and 0.5°C colder than any previous observation. Four transect lines off the coast of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 16 publications
3
59
0
Order By: Relevance
“…Although there were differences between the procedures used for this analysis and the preceding analysis of an open-ocean site, some general conclusions are clear. Like their open-ocean counterparts, the metaproteome of the Oregon shelf SAR11 population was dominated by transport proteins, but the main targets for transport in this productive system were predominantly carbon-and nitrogencontaining compounds, rather than phosphate, supporting the developed ecological theory for this region, which predicts that nitrogen, rather than phosphorous, is ultimately the nutrient that limits productivity (Wheeler et al, 2003).…”
Section: Discussionmentioning
confidence: 83%
“…Although there were differences between the procedures used for this analysis and the preceding analysis of an open-ocean site, some general conclusions are clear. Like their open-ocean counterparts, the metaproteome of the Oregon shelf SAR11 population was dominated by transport proteins, but the main targets for transport in this productive system were predominantly carbon-and nitrogencontaining compounds, rather than phosphate, supporting the developed ecological theory for this region, which predicts that nitrogen, rather than phosphorous, is ultimately the nutrient that limits productivity (Wheeler et al, 2003).…”
Section: Discussionmentioning
confidence: 83%
“…[17] The observed cold halocline water is accompanied by high nutrients [Wheeler et al, 2003] which, when upwelled over the shelf, fuel an increase in the amount of primary productivity off the Pacific Northwest [Wheeler et al, 2003;Thomas et al, 2003]. Further, an anomalously high amount of primary productivity could result in an excess of organic material falling to the bottom over the Oregon continental shelf which through respiration may lead to hypoxic bottom water conditions as observed during summer 2002 [Wheeler et al, 2003;B.…”
Section: Discussionmentioning
confidence: 99%
“…5) was 75% higher than normal, and oceanic DIN input was 45% higher than normal (Table 4). Other studies on the shelf off of Newport, Oregon found that 2002 was an anomalous year with the halocline water about 1°cooler, the nutrients (NO 3 − and PO 4 −3 ) 60% higher, and nearshore chlorophyll a 54% higher than in previous years (1998Wheeler et al 2003). Thomas et al (2003) found that during 2002 there were higher than average chlorophyll a concentrations over the entire shelf from British Columbia to northern California.…”
Section: Oceanic Inputmentioning
confidence: 99%
“…Thomas et al (2003) found that during 2002 there were higher than average chlorophyll a concentrations over the entire shelf from British Columbia to northern California. The higher than normal nutrients resulted in increases in phytoplankton standing stock and primary productivity and concurrent decreases in dissolved oxygen over the inner shelf (Wheeler et al 2003;Grantham et al 2004). These anomalous conditions during 2002 have been attributed to the advection of a Subarctic water mass (Barth 2003;Freeland et al 2003;Kosro 2003).…”
Section: Oceanic Inputmentioning
confidence: 99%